2015
DOI: 10.1128/jb.00142-15
|View full text |Cite
|
Sign up to set email alerts
|

Critical Components of the Conjugation Machinery of the Integrative and Conjugative Element ICE Bs1 of Bacillus subtilis

Abstract: Conjugation, or mating, plays a profound role in bacterial evolution by spreading genes that allow bacteria to adapt to and colonize new niches. ICEBs1, an integrative and conjugative element of Bacillus subtilis, can transfer itself and mobilize resident plasmids. DNA transfer is mediated by a type IV secretion system (T4SS). Characterized components of the ICEBs1 T4SS include the conserved VirB4-like ATPase ConE, the bifunctional cell wall hydrolase CwlT, and the presumed VirD4-like coupling protein ConQ. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 57 publications
2
37
0
Order By: Relevance
“…We found that both conG ICEBs1 and conG ICEBat1 complemented the transfer defect caused by the loss of conG in ICEBs1. As determined previously, conG ICEBs1 fully restored transfer to wild type levels (Babic et al, 2011;Leonetti et al, 2015). conG ICEBat1 largely restored conjugation, but to levels ~10-fold lower than those with con-G ICEBs1 (Fig.…”
Section: Cong and Yddj Determine Exclusion Specificitysupporting
confidence: 84%
See 4 more Smart Citations
“…We found that both conG ICEBs1 and conG ICEBat1 complemented the transfer defect caused by the loss of conG in ICEBs1. As determined previously, conG ICEBs1 fully restored transfer to wild type levels (Babic et al, 2011;Leonetti et al, 2015). conG ICEBat1 largely restored conjugation, but to levels ~10-fold lower than those with con-G ICEBs1 (Fig.…”
Section: Cong and Yddj Determine Exclusion Specificitysupporting
confidence: 84%
“…The donor strain MA980 contains the peptidase deletion of cwlT , cwlT Δ( 207‐327 ), described previously (Dewitt and Grossman, ). Donor strains containing a deletion of conG , Δ conG ( 5‐805 ) were derived from MMB1283 (Leonetti et al , ). Donor strains containing a deletion of conQ , Δ conQ848 , were derived from CAL848 (Lee et al , ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations